2005
DOI: 10.5194/acp-5-941-2005
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric methane and carbon dioxide from SCIAMACHY satellite data: initial comparison with chemistry and transport models

Abstract: Abstract. The remote sensing of the atmospheric greenhouse gases methane (CH 4 ) and carbon dioxide (CO 2 ) in the troposphere from instrumentation aboard satellites is a new area of research. In this manuscript, results obtained from observations of the up-welling radiation in the near-infrared by SCIAMACHY on board ENVISAT are presented. Vertical columns of CH 4 , CO 2 and oxygen (O 2 ) have been retrieved and the (air or) O 2 -normalised CH 4 and CO 2 column amounts, the dry air column averaged mixing ratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
255
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(264 citation statements)
references
References 27 publications
7
255
0
2
Order By: Relevance
“…The combined datasets provide the longest time series of globally averaged CH 4 abundance. Since the early 2000s, remotely sensed retrievals of CH 4 have provided CH 4 atmospheric columnaveraged mole fractions (Buchwitz et al, 2005a;Frankenberg et al, 2005;Butz et al, 2011;Crevoisier et al, 2009;. Fourier transform infrared (FTIR) measurements at fixed locations also provide methane column observations .…”
Section: Atmospheric Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined datasets provide the longest time series of globally averaged CH 4 abundance. Since the early 2000s, remotely sensed retrievals of CH 4 have provided CH 4 atmospheric columnaveraged mole fractions (Buchwitz et al, 2005a;Frankenberg et al, 2005;Butz et al, 2011;Crevoisier et al, 2009;. Fourier transform infrared (FTIR) measurements at fixed locations also provide methane column observations .…”
Section: Atmospheric Observationsmentioning
confidence: 99%
“…The atmospheric observation density has improved in the tropics with satellite-based column-averaged methane mixing ratios (Buchwitz et al, 2005b;Frankenberg et al, 2005;Butz et al, 2011). However, the optimal usage of satellite data remains limited by systematic errors in satellite retrievals (Bergamaschi et al, 2009;Locatelli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Scanning Imaging Absorption Spectrometer for Atmospheric Chartography (SCIAMACHY) on the Environmental Satellite (EN-VISAT) first observed CO 2 column-averaged dry-air mole fractions (XCO 2 ) from spectra at 1.57 µm (Buchwitz et al, 2005;Barkley et al, 2006). The Thermal and Near Infrared Sensor for Carbon Observation (TANSO)-Fourier Transform Spectrometer (FTS) on board the Greenhouse Gases Observing Satellite (GOSAT), which was launched in 2009 (Yokota et al, 2009), has observed XCO 2 with high precision by utilizing the 1.6 and/or 2.0 µm CO 2 absorption bands (Yoshida et al, 2011O'Dell et al, 2012;Butz et al, 2011;Cogan et al, 2012).…”
Section: N Saitoh Et Al: Validation Of Tanso-fts Tir V1 Utls Co 2 Pmentioning
confidence: 99%
“…SCIAMACHY was launched on the Envisat platform in 2001 and measures reflected sunlight at UV-SWIR wavelengths, with peak sensitivity near the surface. Buchwitz et al (2005Buchwitz et al ( , 2007, Bösch et al (2006) and Barkley et al (2006) have presented daytime CO 2 retrievals over land from SCIAMACHY data. AIRS was launched on the EOS-Aqua platform in 2002 and different techniques have been used to retrieve atmospheric CO 2 abundances from AIRS radiances.…”
mentioning
confidence: 99%